2011
DOI: 10.1007/s11033-011-0925-9
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for quantitative real-time RT-PCR analysis in citrus

Abstract: Quantitative real-time reverse transcription polymerase chain reaction (qPCR) has become the preferred method for studying low-abundant mRNA expression. Appropriate application of qPCR in such studies requires the use of reference gene(s) as an internal control in order to normalize the mRNA levels between different samples for an exact comparison of gene expression levels. Expression of the reference gene should be independent from development stage, cell/tissue types, treatments and environmental conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 58 publications
3
70
1
4
Order By: Relevance
“…In experiments with cacao, MDH also formed the best combination of reference genes with Rpl35 in tissues inoculated with M. perniciosa (Pinheiro et al, 2011). ACT has been evaluated as a gene reference in various gene expression studies (Liu et al, 2010;Chen et al, 2011), and was considered highly stable when analyzed in various Citrus genotypes (Yan et al, 2012). However, in the present study, ACT was one of the least stable genes, in both non-infected and infected plants.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In experiments with cacao, MDH also formed the best combination of reference genes with Rpl35 in tissues inoculated with M. perniciosa (Pinheiro et al, 2011). ACT has been evaluated as a gene reference in various gene expression studies (Liu et al, 2010;Chen et al, 2011), and was considered highly stable when analyzed in various Citrus genotypes (Yan et al, 2012). However, in the present study, ACT was one of the least stable genes, in both non-infected and infected plants.…”
Section: Discussionmentioning
confidence: 62%
“…The stability of genes that encode ribosomal proteins, such as Rpl35, has been evaluated in many studies, with positive results (Calsa and Figueira, 2007;Schmidt and Delaney, 2010;Pinheiro et al, 2011;Yan et al, 2012). The stability of seven reference gene candidates was analyzed in six Citrus genotypes by Yan et al (2012), and 18SrRNA was found to be one of the most stable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primers used in the RT-qPCR were pth and PR2 previously described by , CALs1 described by and AOS and PR5 described by . Actin and 18S gene expression were used as an internal standard (Yan et al, 2012) (supplementary table 1: primer sequences).…”
Section: Reverse Transcription (Rt-) Pcr Analysis Of Plant Gene Exprementioning
confidence: 99%